(untitled) (International Journal of Engineering and Computer Science, 2017)
Cloud computing users are growing at a rapid rate. The user data is loaded into the cloud. Therefore, the critical data protection is an important issue for any organization regardless of its size. Even though the organizations backup their data manually on a regular basis but the risks of a disaster can’t be avoided. The disasters can be natural or manmade which may lead to sudden and unrecoverable loss of data. This paper discuses the need of cloud backup and provides the detailed insight of the cloud backup solutions employed in the enterprise and small - medium business. In this paper, the technical analysis of the backup solutions is also done using certain parameters like technical support, technical help services etc.